Peran Wisatawan Asing dalam Mendorong Pertumbuhan Ekonomi Lokal di Kawasan Wisata Budaya (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the role of foreign tourists in driving local economic growth in cultural tourism areas. The focus of the study lies in the direct and indirect contribution of tourist activities to increasing community income, developing micro, small, and medium enterprises (MSMEs), and creating jobs around tourist destinations. This study uses a descriptive qualitative approach with a case study at the Maimun Palace, Medan. The results of the study indicate that the arrival of foreign tourists has a positive impact on local economic growth by increasing demand for local products, tourism services, and expanding the market for culture-based creative economies.